Normal Values of Corrected Heart-Rate Variability in 10-Second Electrocardiograms for All Ages - van den Berg, Marten E.; Rijnbeek, Peter R.; Niemeijer, Maartje N.; Hofman, Albert; van Herpen, Gerard; Bots, Michiel L.; Hillege, Hans; Swenne, Cees A.; Eijgelsheim, Mark; Stricker, Bruno H.; Kors, Jan A. (Frontiers in Physiology, 2018)
Purpose: Heart-rate variability (HRV) measured on standard 10-second electrocardiograms (ECGs) has been associated with increased risk of cardiac and all-cause mortality, but age- and sex-dependent normal values have not been established. Since heart rate strongly affects HRV, its effect should be taken into account. We determined a comprehensive set of normal values of heart-rate corrected HRV derived from 10-second ECGs for both children and adults, covering both sexes. Methods: Five population studies in the Netherlands (Pediatric Normal ECG Study, Leiden University Einthoven Science Project, Prevention of Renal and Vascular End-stage Disease Study, Utrecht Health Project, Rotterdam Study) provided 10-second, 12-lead ECGs. ECGs were stored digitally and analyzed by well-validated analysis software. We included cardiologically healthy participants, 42% being men. Their ages ranged from 11 days to 91 years. After quality control, 13,943 ECGs were available. Heart-rate correction formulas were derived using an exponential model. Two time-domain HRV markers were analyzed: the corrected standard deviation of normal-to-normal RR intervals (SDNNc) and corrected root mean square of successive RR-interval differences (RMSSDc). Results: There was a considerable age effect. For both SDNNc and RMSSDc, the median and the lower limit of normal decreased steadily from birth until old age. The upper limit of normal decreased until the age of 60, but increased markedly after that age. Differences of the median were minimal between men and women. Conclusions: We report the first comprehensive set of normal values for heart-rate corrected 10-second HRV, which can be of value in clinical practice and in further research.